LIQUIDITY MANAGEMENT AND QUOTED DEPOSIT MONEY BANKS FINANCIAL PERFORMANCE IN NIGERIA - Nwokoro, A. I.; Ironkwe, U.I.; Nwaiwu, J.N. (American Journals, 2023)
Liquidity Management is one of the most important duties in any company and thus it cannot be overlooked. Sound liquidity management is integral for financial institutions stability and profitability since deteriorating liquidity management is the most recurrent cause of poor financial performance. The aim of this study is to empirically explore the relationship between liquidity management and financial performance of listed deposit money banks in Nigeria. Panel data of the liquidity management and return on equity were collected from the annual report of eight listed international banks on Nigerian Exchange Group from 2010-2020. Ordinary least square regression analysis, Augmented Dickey Fuller Unit root test, Johansen co-integration test, lanrange multiplier test, error correction model were used in analyzing the data. The results indicate that liquidity management significantly relates to return n equity. The study there conclude that there is a strong positive relationship between liquidity management and financial performance and recommend that central bank Nigeria should critically review and follow-up or monitor the effectiveness of liquidity policy tools in banks and where necessary, appropriate sanctions placed on erring banks to ensure effective implementation of these policy tools in an attempt to achieve desired liquidity level.
Keywords: Liquidity, financial performance, return on equity, banks, Nigeria.